Biomass accrual benefits of community-based marine protected areas outweigh their operational costs - Villaseñor-Derbez, Juan Carlos; Fulton, Stuart; Hernández-Velasco, Arturo; Amador-Castro, Imelda G. (Frontiers in Marine Science, 2023)
The costs and benefits of customary top-down Marine Protected Areas (MPAs) have been studied at length. But the costs and benefits of community-based MPAs –an increasingly common tool in conservation and fisheries management– remain understudied. Here, we quantify the operational costs of maintaining community-based MPA monitoring programs in nine small-scale fishing communities in Mexico. We then compare these costs to the potential extractive use value of invertebrate and fish biomass contained in the reserves. We find that the annual monitoring costs (median: 1,130 MXN/ha; range: 23-3,561 MXN/ha) represent between 0.3% and 55% of the extractive use value of the biomass contained in the reserves (median: 21.31 thousand MXN/ha; 5.22 - 49/12 thousand MXN/ha). These results suggest that the direct monetary benefits of community-based marine conservation can outweigh the costs of monitoring programs, providing further support for these types of management schemes. While further research should explore other mechanisms that would allow fishers to leverage the non-extractive use value of reserves (e.g., tourism) or the non-use value (i.e. existence value of biodiversity) to sustainably finance their conservation efforts, a stop-gap measure to ensuring long-term monitoring costs are covered might include limited extractive use of resources contained in the reserves.